Adenomatoid odontogenic tumor associated with an unerupted primary tooth. Issue 6 (November 2020) - Watanabe, Takuma; Mori, Asumi; Nakao, Kazumasa; Bessho, Kazuhisa
Abstract: Adenomatoid odontogenic tumor (AOT) is a benign epithelial tumor that shows duct-like structures. AOT is usually associated with a permanent tooth, and maxillary canines are the most frequently affected. However, an association between intraosseous AOTs and unerupted primary teeth is extremely rare. Herein, we report an unusual case of an AOT associated with an unerupted primary tooth, which we initially attempted to preserve. A 4.5-year-old female with an AOT associated with the primary maxillary left first molar initially underwent surgical enucleation of the lesion, which preserved the tooth without postoperative eruption, followed by curettage and extraction during a second surgery. The maxillary left first premolar, which was positioned mesially to the primary tooth, showed eruption tendencies at 5 years after the initial surgery. The present case demonstrates that AOT should be included in the differential diagnosis for cystic lesions in children, since AOTs can develop around their unerupted primary teeth. Furthermore, while treating AOT, the decision of whether to preserve the associated primary or permanent tooth should be given careful consideration.